IR study of active sites for n-heptane isomerization over MoO3-ZrO2 - Ruslan, Nurun Najwa; Ahmad Fadzillah, Nurrulhidayah; Karim, Ainul Hakimah; Jalil, Aishah Abdul; Triwahyono, Sugeng (Elsevier, 2011)
The property of acidic sites onMoO3-ZrO2 was studied for n-heptane isomerization.A2,6-lutidine IRstudy showed that the introduction of MoO3 on ZrO2 partially eliminated the absorbance band at 1605 cm−1 ascribed to Lewis acid sites corresponding to the presence of the monoclinic phase of ZrO2 and developed several Brönsted and Lewis acid sites with different acidic strengths. MoO3-ZrO2 possesses a large number of relatively weak Lewis and Brönsted acid sites as well as strong acid sites. The active protonic acid sites in n-heptane isomerization were formed from molecular hydrogen through a spillover mechanism with the involvement of doublet bands at 1595 and 1580 cm−1 ascribed to the Lewis acid sites corresponding to the presence of the tetragonal phase of ZrO2. No catalytic activity of MoO3-ZrO2 for n-heptane isomerization was observed in the absence of the doublet bands at 1595 and 1580 cm−1 and hydrogen in the gas phase